High School Students’ Motivation to Learn Climate Change Science through Educational Computer Games - Besalti, Metin; Smith, Glenn Gordon (Simulation & gaming, 2024)
Background Teaching climate change is difficult. Its complexity spans many subjects, often taught disjointedly. Many climate change effects are not immediately observable, making it hard for students to connect to it personally. Aim This study investigates how we can spark high school students’ interest in learning about climate change using educational computer games. Method We adopted a qualitative case research design to understand how games boost students’ drive and their role in motivating them. We selected a high school teacher and her eight students as our subjects, interviewing them in person. We analyzed their responses were using Keller’s ARCS Theory of Motivation Model and blending deductive and inductive methods. Results The findings were encouraging: games positively impacted students’ interest in climate change. They transformed the learning atmosphere into a concentrated, captivating space where the content was seen as tough yet enjoyable. Moreover, the games helped students make real-world connections, enhancing their understanding and appreciation of the topic. Conclusion Educational games are a powerful tool in motivating students to learn about climate change science. Hence, educators should be ready to harness the games’ power to create immersive, fun, and stimulating learning environments.